Meningkatkan Berpikir Kritis Dan Prestasi Belajar Siswa Melalui PBL Berbantuan Multimedia Materi Keberagaman Di Kelas XII F1B SMA Xaverius 1 Jambi - Fajar Arinto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Student activity in learning Catholic Religious Education is still lacking, which has an impact on learning outcomes. This is because in learning activities teachers tend to use conventional methods. A learning method is needed that can stimulate students to be active and able to think critically. This research aims to improve Catholic Religious Education learning outcomes through the application of the Problem Based Learning model assisted by Powerpoint for class XIIF1B students. This type of research is Classroom Action Research (CAR). The research subjects were 31 students in class XII F1B SMA Xaverius 1 Jambi. Data collection in this research was carried out using observation and test methods. The collected data was analyzed using quantitative descriptive analysis. The research results show that students' learning outcomes and critical thinking abilities have increased. The learning outcomes in the material on living together in diversity ended with a learning completion percentage of 100% and the students' critical thinking skills had good criteria.